The Impact Of Auction Price, Inflation, And Exchange Rate Fluctuations On Indian Tea Export Prices (Journal of Namibian Studies : History Politics Culture, 2023)
The global tea market is a pivotal sector in international trade, with India emerging as a significant player. Indian tea exports contribute notably to the economy and reflect the nation's cultural heritage. The complexities of Indian tea exports are shaped by various factors, including auction prices, inflation, exchange rate fluctuations, production patterns, seasonal variations, export quantities, and lending rates. This study comprehensively explores these interconnected influences on export pricing dynamics. The research aims to provide a holistic understanding of the multifaceted determinants of Indian tea export prices, offering valuable insights for strategic decision-making in a competitive global market. By examining historical data from 2015 to 2021 and utilizing regression analysis and automated linear modeling, the study sheds light on the interplay of these factors and their impact on Indian tea's export prices.